Assessing food security performance from the One Health concept: an evaluation tool based on the Global One Health Index - Si-Yu Gu; Fu-Min Chen; Chen-Sheng Zhang; Yi-Bin Zhou; Tian-Yun Li; Ne Qiang; Xiao-Xi Zhang; Jing-Shu Liu; Shu-Xun Wang; Xue-Chen Yang; Xiao-Kui Guo; Qin-Qin Hu; et al. (BMC, 2023)
Abstract Background Food systems instantiate the complex interdependencies across humans, physical environments, and other organisms. Applying One Health approaches for agri-food system transformation, which adopts integrated and unifying approaches to optimize the overall health of humans, animals, plants, and environments, is crucial to enhance the sustainability of food systems. This study develops a potential assessment tool, named the global One Health index-Food Security (GOHI-FS), aiming to evaluate food security performance across countries/territories from One Health perspective and identify relevant gaps that need to be improved for sustainable food systems. Methods We comprehensively reviewed existing frameworks and elements of food security. The indicator framework of GOHI-FS was conceptualized following the structure-process-outcome model and confirmed by expert advisory. Publicly available data in 2020 was collected for each indicator. The weighting strategy was determined by the Fuzzy Analytical Hierarchy Process. The data for each indicator was normalized and aggregated by weighted arithmetic mean. Linear regressions were performed to evaluate the associations of GOHI-FS with health and social-economic indicators. Results The GOHI-FS includes 5 first-level indicators, 19 second-level indicators and 45 third-level indicators. There were 146 countries/territories enrolled for evaluation. The highest average score of first-level indicators was Nutrition (69.8) and the lowest was Government Support and Response (31.3). There was regional heterogeneity of GOHI-FS scores. Higher median scores with interquartile range (IQR) were shown in North America (median: 76.1, IQR: 75.5-76.7), followed by Europe and Central Asia (median: 66.9, IQR: 60.1-74.3), East Asia and the Pacific (median: 60.6, IQR: 55.5-68.7), Latin America and the Caribbean (median: 60.2, IQR: 57.8-65.0), Middle East and North Africa (median: 56.6, IQR: 52.0-62.8), South Asia (median: 51.1, IQR: 46.7-53.8), and sub-Saharan Africa (median: 41.4, IQR: 37.2-46.5). We also found significant associations between GOHI-FS and GDP per capita, socio-demographic index, health expenditure and life expectancy. Conclusions GOHI-FS is a potential assessment tool to understand the gaps in food security across countries/territories under the One Health concept. The pilot findings suggest notable gaps for sub-Saharan Africa in numerous aspects. Broad actions are needed globally to promote government support and response for food security.